2000
DOI: 10.2105/ajph.90.7.1074
|View full text |Cite
|
Sign up to set email alerts
|

HIV-infected parents and their children in the United States

Abstract: OBJECTIVES: This study sought to determine the number, characteristics, and living situations of children of HIV-infected adults. METHODS: Interviews were conducted in 1996 and early 1997 with a nationally representative probability sample of 2864 adults receiving health care for HIV within the contiguous United States. RESULTS: Twenty-eight percent of infected adults in care had children. Women were more likely than men to have children (60% vs 18%) and to live with them (76% vs 34%). Twenty-one percent of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…However, maximizing HRQoL and improving well-being aspects of quality of life among this population, means looking beyond biological markers and the provision of ART alone as being sufficient for an intervention. Women living with HIV compared to HIV-positive men often face different types of life challenges and responsibilities, including lower education [37], transportation challenges to accessing HIV care [38], and having children [39]. Power imbalance in negotiating condom use to partners in KwaZulu-Natal, South Africa [40] is also recognized as one of the factors in contributing to the transmission of HIV/AIDS in this region.…”
Section: Discussionmentioning
confidence: 99%
“…However, maximizing HRQoL and improving well-being aspects of quality of life among this population, means looking beyond biological markers and the provision of ART alone as being sufficient for an intervention. Women living with HIV compared to HIV-positive men often face different types of life challenges and responsibilities, including lower education [37], transportation challenges to accessing HIV care [38], and having children [39]. Power imbalance in negotiating condom use to partners in KwaZulu-Natal, South Africa [40] is also recognized as one of the factors in contributing to the transmission of HIV/AIDS in this region.…”
Section: Discussionmentioning
confidence: 99%
“…The focus on immediate survival from an acute infection has gradually shifted to an increased awareness for living with a protracted illness, and improvements in the quality of life (QoL). As perceptions and treatment procedures have evolved, HIV-related issues were also becoming a prolonged or lifetime challenge for people living with HIV (PLH) and their family members [1ā€“5]. Recent studies on PLH in Thailand suggested that familial factors, such as family relationships and functioning, influenced QoL [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, 28% of adults infected with HIV are parents (Schuster et al, 2000). Among families affected by parental HIV, research consistently has shown the significant effects of maternal HIV status and distress on adolescent outcomes (Bauman, Silver, Draimin, & Hudis, 2007; Biggar et al, 2000; Forehand et al, 1998; Lester, Stein, & Bursch, 2003; Rotheram-Borus, Lee, Lin, & Lester, 2004; Rotheram-Borus, Stein, & Lester, 2006).…”
Section: Introductionmentioning
confidence: 99%